Brexit and the EEA Agreement. The Effects of Brexit on the UK's Contracting Party Status Under the EEA Agreement - Reynir Ingi Reinhardsson 1989- (2018)
Following UK’s decision to withdraw from the European Union, the question on UK’s future relationship with the EU, and especially its possible continuing access to the single market, became one of the main focus points of the whole Brexit debate. The EEA Agreement extends the single market of the EU to the three EEA-EFTA States of Iceland, Norway and Liechtenstein. The UK is currently a Contracting Party to the EEA Agreement in its capacity as a Member States of the EU. However, following UK’s withdrawal from the EU the question arises what consequences it will entail for the EEA Agreement? What options does the UK face concerning its Contracting Party Status to the Agreement? Can the UK retain its Contracting Party Status even after formally withdrawing from the EU? This paper examines the three legal options facing the UK concerning its future participation in the EEA Agreement. These options are: 1) The UK chooses to invoke the withdrawal procedure of Article 127 EEA and formally withdraw from the EEA Agreement; 2) the UK chooses not to invoke Article 127 EEA and; 3) the UK chooses to remain a Contracting Party to the EEA Agreement. The paper provides an overall assessment of these option by examining the legal processes envisaged both in EU law and EEA law, and the relationship between the two legal orders. Furthermore, the relevance of public international law in this regard is examined. However, the main focus point will be on option two, and the main research question that this paper examines, which is whether the UK can retain its Contracting Party Status to the EEA Agreement post-Brexit. Arguments put forward by legal scholars who argue that the UK can retain its Contracting Party Status are examined, along with arguments that support the opposing view. In addition, the author of this paper will provide his own assessment and view of these arguments in order to definitely answer the main research question. A lot of literature exists on the withdrawal process of Article 50 TEU, however, less has been ...